Kajian Potensi Peningkatan Daya Terpasang PLTA Sebagai Pemanfaatan Surplus Debit Air Unit PLTA Batang Agam - Kurniawan, Elfin; Hakam, Dzikri Firmansyah; Prahastono, Iswan; Nainggolan, Akiman (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2021)
Batang Agam hydro Power Plant is a run of river hydro Power Plant which operated in 1976 with initially 2 (two) generation units operation. In 1981, the Batang Agam hydro Power Plant experienced 1 (one) unit expansion, resulted in total capacity of 3 x 3,5 MW. Based on the analysis carried out by the author, we found that there are potential for additional generating power from the existing river flow. This analysis based on 3 (three) types of studies, namely the study of excess inlet water discharge (inflow) at the overflow point in the tando pond spillway, the study of excess inflow at the overflow point in the spillway sand pond, and the study of water savings from modification of the tando pond screen outlet. Moreover, this research conducts a study on the capacity of additional units and the capacity of the existing waterway to determine the durability of the infrastructure. Based on the study results, an inflow surplus of 2,58 m3/s was obtained with a potential additional unit capacity of 2 MW. After more than 40 years of operation, the main hydropower facilities experience several modifications in the intake and the tando pond. We identified the potential to increase the installed power capacity of the Batang Agam Hydroelectric Power Plant by utilizing the surplus water in the tando and sand pond. The utilization of this water surplus can convert hydro energy into electrical energy that produce an additional 1 x 2 MW generator unit. This research provides a beneficial to PLN in increasing power supply to the interconnection system without land acquisition by utilizing the existing waterway.